‘E pluribus unum......forum?’ A Marxist approach to the EU’s democratic deficit - Dimitrios Kivotidis (European Law Open)
This article approaches the issue of the European Union’s (EU) democratic deficit from a Marxist perspective. This issue has been central to the exponential rise of Euroscepticism that influenced processes like Brexit and Grexit (despite the latter’s frustration), as well as the rise of explicitly anti-EU national governments in European countries. This article shows that critiques of the EU’s democratic deficit (even cutting-edge ones, like the one placing emphasis on the notion of the ‘economic constitution’) are inadequate because the debate is already embedded in ideological compromise. Offering a brief exposition of the Marxist approach to the democratic form of the capitalist state, it attempts to show the limitations of critical approaches which overlook the issue of class rule and state power in their calls for democratisation. To do so, the article outlines the structural function and class character of the EU, as well as its role as a (supra-)state formation in the process of capital accumulation. Ultimately, it offers a Janus-faced critique of democratic deficit in Europe, one the one hand arguing that the critique of the EU economic constitution as neoliberal is limited because it fails to account for the scope of reform that the EU allows to respond to the challenges of the process of capital accumulation, while on the other concluding that the solution to the democratic deficit cannot simply be a return to nation-state democracy which is equidistant from actual self-government of the popular strata as its EU counterpart.